Pelatihan Literasi Bahasa Ibrani Alkitabiah Secara Daring bagi Masyarakat Kristen Lintas Daerah - Dwiyono, Dwiyono (Journal Of Social Empowerment Publications, 2025)
Limited access to Biblical Hebrew learning resources has often hindered non-academic Christian communities from engaging the Scriptures in their original language. This community service program aims to empower Christians from diverse regions through an accessible and contextual online literacy training in Biblical Hebrew. The program employed a narrative review to design learning materials and implemented interactive lectures via Zoom for delivery. Results indicate significant cognitive and affective improvement among participants—from having no prior knowledge to reading and interpreting verses in Hebrew. Beyond linguistic competence, the program also strengthened participants’ spiritual convictions and fostered a cross-regional learning community. Training sessions were documented and shared through digital platforms to reach independent learners more broadly. In conclusion, this initiative demonstrates that Biblical Hebrew education can be developed inclusively and technologically outside of formal institutions for wider community benefit.